2023
DOI: 10.3390/electronics12010237
|View full text |Cite
|
Sign up to set email alerts
|

Decentralized Energy Management System in Microgrid Considering Uncertainty and Demand Response

Abstract: Smart energy management and control systems can improve the efficient use of electricity and maintain the balance between supply and demand. This paper proposes the modeling of a decentralized energy management system (EMS) to reduce system operation costs under renewable generation and load uncertainties. There are three stages of the proposed strategy. First, this paper applies an autoregressive moving average (ARMA) model for forecasting PV and wind generations as well as power demand. Second, an optimal ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Wynn et al 74 presented decentralized EMS to diminish the operation cost of the system under the generation of renewable sources and load uncertainties. At first, the PV, wind, and power demand was forecasted by the autoregressive T A B L E 1 Analysis of the centralized and decentralized energy management systems (EMS) schemes available.…”
Section: Decentralized Emsmentioning
confidence: 99%
“…Wynn et al 74 presented decentralized EMS to diminish the operation cost of the system under the generation of renewable sources and load uncertainties. At first, the PV, wind, and power demand was forecasted by the autoregressive T A B L E 1 Analysis of the centralized and decentralized energy management systems (EMS) schemes available.…”
Section: Decentralized Emsmentioning
confidence: 99%
“…Second, an optimal generation scheduling procedure is intended to reduce system operating expenses. The simulation results indicated that the optimal generation scheduling could minimize operating expenses under the worst-case scenario [31]. In [32], combining two models, the ARMA and nonlinear auto regressive with exogenous input (NARX), a novel method was presented for predicting solar radiation.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the proposed study indicate a significant reduction in energy cost bills and an improvement in renewable power generation. Wynn et al [34] modelled a decentralized energy management system to reduce operational costs under RES. The model applies PSO for optimal RES generation and load demand schedule.…”
Section: Introductionmentioning
confidence: 99%